2000
DOI: 10.1111/0033-3352.00096
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Patterns of Support for Privatization in the Mass Public: The Case of Michigan

Abstract: This article examines public attitudes about using for‐profit firms or nonprofit organizations to deliver public services in Michigan. Using survey data, it shows how the public reacts to the privatization of various state and local government services. It then considers some dimensions of attitudes toward privatization. Finally, it estimates models that predict support for privatization based upon a range of characteristics of respondents to our survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
75
3
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 6 publications
2
75
3
3
Order By: Relevance
“…The following students assisted in gathering and coding data: Justin Deno, Kamra Krueger, Frank Leung, Aprameya Mysore, Natalie Neals, Rachel Sperling, and Elizabeth Wansley.5 The claim here is not that newspaper coverage is representative of public opinion, but that newspapers capture salient strands of discourse in the public debate. As a practical matter, there are no appropriate surveys on which to base a comparison between newspaper coverage and public opinion (seeThompson and Elling 2000).6 The following calculations refer to custodial (rather than jurisdictional) inmate populations and they omit federally contracted facilities.7 Figures for 1990 refer to midyear inmate counts. Figures for 2005 (below) refer to yearend inmate counts.…”
mentioning
confidence: 99%
“…The following students assisted in gathering and coding data: Justin Deno, Kamra Krueger, Frank Leung, Aprameya Mysore, Natalie Neals, Rachel Sperling, and Elizabeth Wansley.5 The claim here is not that newspaper coverage is representative of public opinion, but that newspapers capture salient strands of discourse in the public debate. As a practical matter, there are no appropriate surveys on which to base a comparison between newspaper coverage and public opinion (seeThompson and Elling 2000).6 The following calculations refer to custodial (rather than jurisdictional) inmate populations and they omit federally contracted facilities.7 Figures for 1990 refer to midyear inmate counts. Figures for 2005 (below) refer to yearend inmate counts.…”
mentioning
confidence: 99%
“…Support for fiscal stress strategies in the context of different services Thompson and Elling (2000) have shown that the support expressed by Michigan residents for contracting varied significantly across service areas, but support for other possible strategies to address fiscal stress has not been examined in this way. The respondents in this study were asked to indicate their support for the eight strategies to confront revenue shortfalls in the following five services:…”
Section: Strategies For Coping With Fiscal Stressmentioning
confidence: 99%
“…While each of these is a core service regularly provided by municipal governments in Michigan and the US (Citizens Research Council of Michigan 2005), as a group they differ in terms of potential production economies, likely transaction costs created when contracting for the service, the application of police or regulatory power, historical experience as a contracted service and the visibility of the service to the public (Brown andPotoski 2003, Thompson andElling 2000).…”
Section: Strategies For Coping With Fiscal Stressmentioning
confidence: 99%
“…De Groot & Pommer, 1989;Kemp & Willetts, 1995;Tan & Murrell, 1984). In the only previous study that we have located on preferences in who should supply services, Thompson and Elling (2000) surveyed residents of the state of Michigan, and found a majority in favour of government provision for 10 of the 14 services. Regression was used to predict support for privatisation from a range of demographic variables.…”
Section: Introductionmentioning
confidence: 95%